Probability theory and public-key cryptography. Issue 4 (2nd October 2021) - Bessonov, Mariya; Grigoriev, Dima; Shpilrain, Vladimir
Abstract : In this short note, we address a common misconception at the interface of probability theory and public-key cryptography.